Biomarkers for personalized medicine in GI cancers. (November 2015) - Zhang, Shuang Yin; Zhang, Shuang Qin; Nagaraju, Ganji Purnachandra; El-Rayes, Bassel F.
Abstract: Gastrointestinal malignancies are a major health care challenge due to the high incidence and overall poor outcome. A biomarker is a molecular characteristic of a tumor that may be utilized in the initial risk assessment and the subsequent management of the patient. This review focuses on the most pertinent prognostic and predictive biomarkers used in the clinical management of gastric, pancreas, and colon cancer. The available assays, limitations and clinical use for each biomarker are reviewed. The clinical trials evaluating novel biomarkers in GI cancers are discussed.